Modeling of hybrid EDFA/DRA : theory, numerical simulation and experimental evaluation - Naji, Ahmed Wathik; Hossain, Nadir (Lambert Academic Publishing (LAP), 2010)
This book focuses on the modeling of hybrid EDFA/ DRA for long haul optical fiber communication system. The mathematical model of hybrid EDFA/DRA is represented by two separate models. The first model deals with the modeling of double pass Erbium doped fiber amplifier (EDFA) and the second model deals with the modeling of distributed Raman amplifier (DRA). These two models are integrated in order to model the hybrid EDFA / DRA. A mathematical model of DP EDFA is developed. A combination of Runge-Kutta method and relaxation method is used to numerically solve the developed DP EDFA mathematical model. The numerical results are used to describe the design process of an optimized DP EDFA. The DP EDFA mathematical model is validated with the help of previously published experimental results. A mathematical model of DRA is developed. An approach to numerically solve the developed DRA mathematical model is described. Numerical results are used to characterize the DRA. The DRA mathematical model is validated with the help of previously published experimental results.